2013
DOI: 10.4172/2157-7439.1000171
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization with TAT-Peptide Enhances Blood-Brain Barrier Crossing In vitro of Nanoliposomes Carrying a Curcumin-Derivative to Bind Amyloid-Β Peptide

Abstract: # These authors contributed equally to this work preventing high-molecular weight molecules from passing through [25]. Indeed, the design and engineering of NP with high specificity for brain capillary endothelial cells have been proposed as promising strategy for AD diagnosis and treatment [26][27][28][29].The aim of the present investigation was to design NP able to bind Aβ peptide and to cross the BBB. To reach this goal we developed nanoliposomes (NL) double-functionalized with a curcuminderivative and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…Among all CPPs, the modified HIV-1 transactivating transcriptional activator (TAT) peptide (having positive charges that can interact with negative charges of the BBB) has been successfully used for specific endocytosis delivery of liposome nanoparticles into the brain [224]. It has been demonstrated that nanoliposomes double-functionalized with a CUR derivative and with a TAT peptide enhances BBB crossing in vitro, carrying a CUR-derivative to bind Aβ peptide [225]. Also, CUR derivatives containing lipid ligands can be exploited for targeted drug delivery for brain diseases.…”
Section: Liposomesmentioning
confidence: 99%
“…Among all CPPs, the modified HIV-1 transactivating transcriptional activator (TAT) peptide (having positive charges that can interact with negative charges of the BBB) has been successfully used for specific endocytosis delivery of liposome nanoparticles into the brain [224]. It has been demonstrated that nanoliposomes double-functionalized with a CUR derivative and with a TAT peptide enhances BBB crossing in vitro, carrying a CUR-derivative to bind Aβ peptide [225]. Also, CUR derivatives containing lipid ligands can be exploited for targeted drug delivery for brain diseases.…”
Section: Liposomesmentioning
confidence: 99%
“…In vitro, nanoliposomes of Cur or Cur derivatives were able to control or decrease the Aβ oligomers or the fibril formation (Taylor et al, 2011). A double-functionalized nanoliposomes of a Cur derivative in modified HIV Trans-activating Transcriptional Activator (TAT) peptide (TATCur-NL) could cross the BBB in vitro and illustrated high affinity for Aβ peptides (Sancini et al, 2013). In another in vitro study, apolipoprotein E3 mediated poly(butyl) cyanoacrylate NPs containing Cur (ApoE3-C-PBCA), enhanced the photostability and the cellular uptake of Cur due to a sustained drug release (Mulik et al, 2010).…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Liposomes functionalized with TAT-peptide In vitro Permeability across the BBB enhanced [98]. Increased entrapment efficiency of NGF and CU, of NGF release and cell viability, Decreased release of CU, Permeability of NGF and CU across the blood-brain barrier [102].…”
Section: Admentioning
confidence: 99%